Time effect on structural and functional properties of whey protein isolate‐gum acacia conjugates prepared via Maillard reaction. (7th May 2019) - Chen, Weijun; Lv, Ruiling; Wang, Wenjun; Ma, Xiaobin; Muhammad, Aliyu Idris; Guo, Mingming; Ye, Xingqian; Liu, Donghong
Abstract: BACKGROUND: The functional properties of whey protein isolate (WPI) are sensitive to pH, ionic strength, and temperature. This prevents its application in various food systems and processing technologies. The conjugation of proteins with polysaccharides via the Maillard reaction is an efficient method to improve the functionality of proteins. The purpose of this work was to conjugate gum acacia (GA) with WPI via the dry‐heating Maillard reaction and to investigate the effect of reaction time on the physicochemical and functional properties of WPI‐GA conjugates. RESULTS: Sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and high‐performance size exclusion chromatography confirmed the formation of higher molecular weight conjugates. The degrees of glycation for WPI‐GA conjugates incubated for 1, 3, 5, and 7 days were 28.14%, 44.98%, 49.50%, and 51.20%, respectively. The glycation reaction reduced the surface hydrophobicity and fluorescence intensity of WPI significantly ( P  < 0.05). Functional properties of the conjugates, such as solubility, stability against heat‐induced insolubility, and emulsion properties were all superior to the control WPI. However, a reaction time longer than a day resulted in a high degree of browning and decreased the functionality of the conjugate significantly ( P  < 0.05). CONCLUSION: The results indicated that conjugation of WPI with GA can be a promising way to enhance its functional properties. However, the reaction time suitable for producing conjugates with superior functional properties was not necessarily the highest glycation degree that could be reached. © 2019 Society of Chemical Industry